Descriptions of two new species of Fibuloides Kuznetsov, 1997 (Lepidoptera: Tortricidae: Eucosmini) from Thailand - Siraphattarathamrong, Paphatpron; Muadsub, Sopita; Pinkaew, Nantasak (Zootaxa, 2019)
Two new species of genus Fibuloides, F. bacriora Siraphattarathamrong and Pinkaew, n. sp., and F. falcatus Siraphattarathamrong and Pinkaew, n. sp., are described from Thailand. Adults and genitalia are illustrated. The two new taxa increase the number of described Fibuloides species in Thailand to 17.